Efektifitas Rebusan Air Daun Sirih Dalam Perawatan Dermatitis Dalam Konsep Asuhan Keperawatan di Kelurahan Pandan Kasturi RT/RW: 01/01 Kecamatan Sirimau Kota Ambon - Ellen Lombonanung (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Occupational skin disease is a skin disorder that occurs due to a person's work and is commonly found in industrial, agricultural, and plantation areas. This disease is caused by materials/substances and processes carried out in the workplace generally and is known as dermatitis. Atopic dermatitis has dry skin and often has itching, allergic rhinitis, nasal obstruction, conjunctiva and pharynx itching, lacrimation, and seasonality when associated with pollen. This study uses a descriptive case study method where the researcher will describe the case experienced by a client with dermatitis. Respondents in this case study were Mr. N who has been experiencing dermatitis for ± 2 weeks in the pandan kasturi village RT / RW: 01/01 which was carried out for 3 days (November 27, 2023-30 November 2023). The results showed that during the 3 days of implementing dermatitis treatment with siri leaf decoction water, there were changes from Mr. N's complaints. Mr. N said the itching on his feet and hands and between his fingers decreased, did not feel itchy at night after treatment with siri leaf decoction water, redness and wounds due to frequent scratching seemed to decrease. It can be concluded that betel leaf cooking water is effective for the treatment of itching in dermatitis.